Izydora z Sewilli "De ortu et obitu patrum": studium źródeł traktatu - Krynicka, Tatiana (Vox Patrum, 2022)
Isidore of Seville’s treatise De ortu et obitu patrum is a remarkably intertextual work. The Holy Writ is its fundamental hypotext. While referring biblical Salvation history, Isidore demonstrates his acquaintance with the numerous writings of different authors. Tracing of the relations between selected chapters of the treatise (1. Adam; 26. Aaron; 41. Hosea; 45. Jonah; 59. The three young men [in the blazing furnace]) and their sources and models let us come to the conclusion that Isidore demonstrates his writer’s independence as well when composing the majority of particular relations (precisely those based on sources other than biblical vitae), as when creating the conception of the entire work, which can be regarded as a hybrid of exegesis and hagiography, and had not had a prototype in the earlier Christian literature.